Establishment of a new genus for Asthenognathus gallardoi Serène & Soh, 1976 within Gaeticinae Davie & N.K. Ng, 2007 (Crustacea: Decapoda: Brachyura: Varunidae) - Naruse, Tohru; Clark, Paul F. (Zootaxa, 2009)
Recently collected Asthenognathus gallardoi Serène & Soh, 1976 from Thailand and the Philippines are examined. Asthenognathus gallardoi possesses long setae of the palp of the third maxilliped and the fused male abdominal segments that are diagnostic characters of Gaeticinae Davie & N.K. Ng, 2007. Although the species lacks the longitudinal sulcus on the anterior segments of the sternum, which is another diagnostic character of Gaeticinae, the anterior part of the sternum is gently concave. The presences of these features indicate that Asthenognathus gallardoi belongs to Gaeticinae, not Asthenognathinae Stimpson, 1858. A new genus is established for Asthenognathus gallardoi to accommodate it in Gaeticinae.